The study on a relationship between work performance and the need of training among UiTM Pahang support staff: a case study / Ahmad Amir Ithnin, Noor Azleen Zainuddin and Mohd Fahmi Mustafar Kamar - Ithnin, Ahmad Amir; Zainuddin, Noor Azleen; Mustafar Kamar, Mohd Fahmi (2012)
In the modernization era, in all organization every employee will be measured by their work performance. Work performance can be explained as a measure performance involves ratings of individuals by someone other than the person whose performance is being considered (Kanter as cited in Intan, C.F. Ho and Maria Carmen Galang 2010). In other opinion, work performance can be describe as an innovative work behavior such as the ability to generate, promote, and realizing creative ideas in the work place is known to be important and beneficial to the organizational success (Janssen, 2000). Whereas for training it can be describe as a planned effort by a company to facilitate employees' learning on job related competencies (Noe, 2010). Training is often used to describe effort initiated by organization, in other words, to foster learning among its employee (Snell and Bohlander, 2010). Organization has a big responsibility to encourage their employee to improve their work performance. As a result, it will lead the organization to a better future because of the effectiveness in implementing Human Resources practices such as training (Intan et.al., 2011). A good training program can give a lot of benefits to the employee. It will help the employees to master the knowledge, skill and ability in order to do their work well. It is also can enhance their behavior that has been emphasized during the training programs. According to Menguin, (2010) by providing training to employees is not only will helps them develop their skills and knowledge, but it is also act as a motivation for employee and also act as a building block because nowadays organization thrive for success.